CCBD's Position Summary on the Use of Physical Restraint Procedures in Educational Settings. (November 2020) - ,
This document provides policy recommendations of the Council for Children with Behavioral Disorders (CCBD) regarding the use of physical restraint procedures in educational settings. It includes (a) an introduction with definitions of terminology; (b) a discussion of the problems with the use of physical restraint, policy on this topic, and the lack of research; (c) a Declaration of Principles; and (d) Recommendations Regarding the Use of Physical Restraint in educational settings. Although the policy recommendations in this document pertain to the United States, we believe the principles and nonpolicy recommendations are equally applicable to other countries.